2020
DOI: 10.1186/s12974-020-01926-x
|View full text |Cite
|
Sign up to set email alerts
|

Rh-relaxin-2 attenuates degranulation of mast cells by inhibiting NF-κB through PI3K-AKT/TNFAIP3 pathway in an experimental germinal matrix hemorrhage rat model

Abstract: Background: Mast cells play an important role in early immune reactions in the brain by degranulation and the consequent inflammatory response. Our aim of the study is to investigate the effects of rh-relaxin-2 on mast cells and the underlying mechanisms in a germinal matrix hemorrhage (GMH) rat model. Methods: One hundred seventy-three P7 rat pups were subjected to GMH by an intraparenchymal injection of bacterial collagenase. Clodronate liposome was administered through intracerebroventricular (i.c.v.) injec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Many of the effects of human gene-2 relaxin (H2 relaxin) are mediated by its homologous G protein-coupled receptor (GPCR) and relaxin family peptide receptor (RXFP1). For example, the activation of RXFP1 by rh-RLN2 can improve mast cell degranulation and neurological function by inhibiting NF-κB of PI3K-AKT/neoplasm necrosis factor-alpha-induced protein 3 (TNFAIP3) signaling pathway, which indicated that rh-RLN2 may be a promising therapeutic agent to reduce neuroinflammation and secondary brain injury in germinal matrix hemorrhage patients ( 39 ). RLN-2 produces endothelium- and NO-dependent relaxation of mouse mesenteric arteries by activation of RXFP1 coupled to Gi2-PI3K-eNOS pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Many of the effects of human gene-2 relaxin (H2 relaxin) are mediated by its homologous G protein-coupled receptor (GPCR) and relaxin family peptide receptor (RXFP1). For example, the activation of RXFP1 by rh-RLN2 can improve mast cell degranulation and neurological function by inhibiting NF-κB of PI3K-AKT/neoplasm necrosis factor-alpha-induced protein 3 (TNFAIP3) signaling pathway, which indicated that rh-RLN2 may be a promising therapeutic agent to reduce neuroinflammation and secondary brain injury in germinal matrix hemorrhage patients ( 39 ). RLN-2 produces endothelium- and NO-dependent relaxation of mouse mesenteric arteries by activation of RXFP1 coupled to Gi2-PI3K-eNOS pathway.…”
Section: Resultsmentioning
confidence: 99%
“…It is both deubiquitinating and is an ubiquitin ligase. The vital involvement of this protein in regulating inflammatory signal transduction [ 15 , 16 ] to negatively regulate the NF- κ B pathway via feedback and inhibit NF- κ B pathway activation via several inflammatory signals has been shown [ 17 20 ]. It can inhibit the transcription of downstream inflammatory factors and has a strong anti-inflammatory effect.…”
Section: Discussionmentioning
confidence: 99%
“…Silencer siRNA Transfection Kit (Thermo Fisher Scientific, Waltham, MA, USA) was used for the knockdown of selected genes (NF-κB, c-Myc and STAT3), according to the manufacturer’s instructions ( Figure S1 ). The transcription factors were selected according to the literature, as the factors involved in the process of airway remodeling, but also as suggested elements of the relaxin pathway in this process [ 23 , 101 , 102 , 103 , 104 , 105 ]. The cells were treated with 20 nM siRNA mixture against NF-κB (NCBI accession no.…”
Section: Methodsmentioning
confidence: 99%